THE RELATIONSHIP BETWEEN ANXIETY AND EMOTIONAL REGULATION WITH BLOOD GLUCOSE LEVEL STABILITY IN TYPE 2 DIABETES MELLITUS POSYANDU ELDERLY PAGU KEDIRI REGENCY - Sutik; Erva Elli Kristanti; Puguh Santoso (Suluh Adiluhung Publisher (SAPub), 2025)
Type 2 diabetes mellitus is a type of diabetes characterized by high blood sugar (glucose) levels due to persistent disturbances in carbohydrate, fat, and protein metabolism, which can lead to complications if not managed properly. This metabolic disorder is not only related to physiological factors but is also influenced by psychological factors.. The purpose of this study was to determine the Relationship Between Anxiety and Emotional Regulation With Blood Glucose Level Stability in Type 2 Diabetes Mellitus Posyandu Elderly Pagu Kediri Regency. The design of this research is correlational analytic research with cross sectional approach. Population were Type 2 Diabetes Mellitus Patiens Posyandu Elderly Pagu Kediri Regency, using Purposive Sampling technique obtained a sample of 38 respondents. The independent variables studied were Anxiety and Regulation Emotion Level, while the dependent variable were Blood Glucose Level Stability in Type 2 Diabetes Mellitus Patiens. The instrument used was observation. The results were analyzed using the Chi square test (α = 0.05) The results showed that Anxiety level based on the frequency distribution of respondents, almost all of whom had moderate anxiety, namely 18 respondents (47,4%); almost all of whom had moderate regulation emotion level, namely 16 respondents (42,1%); and almost all of whom had high blood glucose level stability, namely 21 respondents (55,2%). Based on data then the results of the analysis using the Chi Square Test show that the p- value is less than α (0.05), because the p-value is <0.05. This shows p value = 0.028 ≤ α = 0.05, This shows p value = 0.017 ≤ α =0.05, so that Ha is accepted, and Ho is rejected. It can be concluded that the Relationship Between Anxiety and Regulation Emotion With Blood Glucose Level Stability in Type 2 Diabetes Mellitus Posyandu Elderly in Pagu Kediri Regency. The importance of the Several psychological interventions for glucose control, including emotional regulation therapy, have shown effectiveness in reducing HbA1c and diabetes-related distress, indicating that emotional management may be an important part of glycemic control in people with Type 2 DM.